Respuesta :

Answer:

g = -48

Step-by-step explanation:

[tex]\frac{3}{2} g+8=\frac{2}{2}g-16[/tex] can be simplified to [tex]\frac{3}{2}g+8=g-16[/tex]

I like to get rid of all fractions so I am going to multiply each term by 2 in order to get rid of the [tex]\frac{3}{2}[/tex] which will give us 3g + 16 = 2g -32

With this equation we can now combine like terms, and we can start by subtracting 2g from both sides to get g + 16 = -32

We can now subtract 16 from both sides which will give us g = -48

ACCESS MORE